دراسة تأثير شاردة اليوروبيوم على تألق بلورة فلوريد الكالسيوم - بطيخ أحمد عبد اللطيف; خضرو أحمد حميد (Latakia University Journal -Basic Sciences Series, 2014)
يعدُّ هذا العمل استمراراً لدراسة أطياف تألق الأشعة السينية X-ray luminescence لبلورات تحتوي في تركيبها على الأكاسيد والفلوريدات. قمنا بدراسة أطياف التألق لبلورة فلوريد الكالسيوم المشابة بشوارد اليوروبيوم Eu3+ بنسب مولية مختلفة (0.01, 0.05, 0.3)%، وقد أظهرت الدراسة قمماً طيفية تألقية عند الأطوال الموجية (288, 425, 550)nm، وبزمن تألق مميز τ=11ns. كما تم تحليل التغير في الشدات التألقية للأطوال الموجية الناتجة عن نسب إشابة مختلفة في بلورة فلوريد الكالسيوم، وتبين بأنها تعود إلى الانتقالات الإلكترونية 4f→5d. أجريت القياسات في جامعة بطرس بورغ التكنولوجية الحكومية، روسيا الاتحادية، 2008. This work , could be considered as a continuous study of the X-ray luminescence spectrum crystals, which contain oxides and fluorides. We studied the X-ray luminescence spectrum of the CaF2 mixed with Eu3+-ion of different molar percents (0.01, 0.05 and 0.3)%. The studying show luminescence- peaks- spectrum at wavelengths (288, 425 and 550) nm and specific luminescence- time τ=11ns. Also we analyzed the variation in luminosity intensities in the wavelengths formed due to that variation in molar percents of the crystals, this could be attributed due to the electronics transition 4f→5d. The measurements were done in Tech-governmental University of Peterburg, Russia, 2008.